An Analysis of Textbook “Preparation for Academic English” in Relation to 21st Century Skills - Khasanah, Nudiya; Antoni, Nur; Hidayat, Hendi (Foreign Language Instruction Probe, 2023)
This research conducted to gather whether these textbook contained 21st century or not in communication, collaborative, critical thinking, flexibility and adaptability, leadership and responsibility, creativity and innovation are the skills that should be included in English tasks in 21st century skills. Then the researches will be spell out the textbook by using analysis. The purpose of this research is to detect what the preparation of academic English textbook coincide with the 21st century skills. Qualitative method was used in this research to reveal the analysis of the researcher. The sample of this research is analysis the content related to suitability of the textbook in 21stcentury.There are still few researchers who examine how 21st century skills is implemented in collage English textbook. As a final note, the researcher advises doing study on how published materials are utilized in courses, schools, and universities throughout the nation because she believes it is crucial to do so in order to achieve the intended learning objectives. Also make them more accurate to be learned for each student and teacher or lecturer. The researcher hopes the further research is more detail and conical to the similar problem to be analyses.